(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The contribution rate of tax revenues in the federal budget is very small compared to the rate of contribution of oil revenues and this leads to negative repercussions on the Iraqi economy and the budget becomes a prisoner of high and low oil prices, and this is a problem that needs to be studied to know the extent of the impact of economic and political decisions on the size of tax revenue and The research goal is determined in studying the effect of amending the Unified Law No (26) of 2019 on the size of annual tax revenues . There is a question that needs to be answered in research, which is: Will the new retirement law lead to a decrease in the amount of tax revenue in Iraq? It was concluded that the decrease in the legal age for teaching in Iraqi universities, the sample of the research will lead to a decrease in income tax revenues and then to a decrease in the revenues of the public budget, and The research has reached the amount of this decrease and what it will bring to the state budget upon retirement and the date of teaching instead in relation to salary only.